1977
DOI: 10.1093/oxfordjournals.aje.a112482
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Keratoconjunctivitis at a Vietnamese Refugee Camp in Florida

Abstract: During the summer of 1975 an ongoing outbreak of conjunctivitis occurred among Vietnamese refugees temporarily housed at a U.S. mainland camp. Twenty-two per cent of surveyed refugees gave a history of the disease and 10% were documented as having clinical conjunctivitis at the time of the survey. Fifty-six per cent of documented cases were in children less than 10 years of age. The attack rate among American camp personnel was 4%. Comprehensive microbiologic analysis revealed multiple potential pathogens in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this report, we have used serologic and restriction enzyme analyses to study Ad8 strains isolated over 19 years. Some viruses were obtained from sporadic EKC cases, but most were isolated from several large outbreaks that occurred in the United States (5,8,17,30,35,38), including one major outbreak in a Vietnamese refugee camp in Florida (52).…”
Section: Of 184 Isolates Of Ad8 Identified In Our Laboratory Betweenmentioning
confidence: 99%
“…In this report, we have used serologic and restriction enzyme analyses to study Ad8 strains isolated over 19 years. Some viruses were obtained from sporadic EKC cases, but most were isolated from several large outbreaks that occurred in the United States (5,8,17,30,35,38), including one major outbreak in a Vietnamese refugee camp in Florida (52).…”
Section: Of 184 Isolates Of Ad8 Identified In Our Laboratory Betweenmentioning
confidence: 99%
“…Another re-port16 described difficulties encountered in typing adenovirus related to types 10 to 19 in an outbreak of keratoconjunctivitis in Bristol. The same problem was encountered in this study, since the hybrid type [10][11][12][13][14][15][16][17][18][19] showed characteristics of type 10 determined by neutralization and of type 19 by hemagglutination inhibition.…”
Section: Discussionmentioning
confidence: 75%
“…Nasir Khisro and Rahman (2010) conclude that poor hygiene practices were due to a lack of resources in their study population. Similarly, three publications (3%) report insufficient handwashing facilities (Giardina et al 2016;CDC 2005;Zweighaft et al 1977). In lieu of formal handwashing facilities, handwashing bags (HWB) were provided in refugee camps in Ethiopia.…”
Section: Bodily Hygienementioning
confidence: 99%
“…Crowded displacement settlements often have a scarcity of personal items, such as towels and clothing. As a result, displaced people commonly share these items, facilitating the transmission of pathogens on fomites (Zweighaft et al 1977;Kim et al 2007). Two publications report that displaced people did not have more than one set of culturally and climate appropriate clothing per person (the Sphere Standard) (Greco et al 1993;Lim et al 2005).…”
Section: Fomite Cleanlinessmentioning
confidence: 99%
See 1 more Smart Citation